Enzyme Typing of Malaria Parasites. Issue 5846 (20th January 1973) - Carter, R.; Voller, A.
Abstract : Analysis of various isolates of Plasmodium falciparum from East and West Africa and from South-east Asia showed that some of the parasite enzymes can exist in more than one electrophoretic form. At least one form of each enzyme was common to parasites from all three regions. The enzyme forms could be used to differentiate morphologically indistinguishable samples of P. falciparum.